Pengelolaan Pendidikan Karakter Demokratis Dalam Pembelajaran PKN Di SMP Negeri 1 Brati Kabupaten Grobogan - MULYONO, PRASETYO EDY, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Ahmad Muhibbin, M.Si (2016)
This research has three aims 1) To determine educational planning the democratic character of students through the study of Civics 2) reach democratic character education of students through learning Civics 3) evaluation of the democratic character of the education of students through learning civics. Data collection techniques by observation, interviews and documentation. Data analysis techniques of data collection, data reduction, data presentation, and conclusion. Test the validity of the data triangulation. The results of this study were (1) the democratic character education planning activities outlined in the lesson plan. In the lesson is listed in the democratic character of the educational value that will be taught students, so that creating awareness for students to practice the democratic values. (2) The teachers of SMP Negeri 1 Brati give opportunities for students to express their opinions about the problems and issues of civics relating to the material being taught. Students are encouraged to fair and boldly expressed his opinion as well as be trained to respect the opinion of the other students.Learning democratic character education can increase society interaction between student by student and student with the teacher. 3) The evaluation results obtained point of view of the student teachers have been changed, the student is no longer as an object of teaching, but the students as active participants teaching in the learning process.